The case of the sneaky snowman eaudiobook - Keene, Carolyn (Nancy Drew and the Clue Crew, 2010)
For budding amateur sleuths, Nancy Drew and her Clue Crew pals George and Bess are the ultimate role models. Winter has come to River Heights, and the girls are busy making a snowman-affectionately named Sherlock. They are distracted, however, by one of their classmates. It seems Deirdre has changed her name to Madame Chocolata, and she's reading marshmallows to tell fortunes. Then Sherlock disappears, and an outbreak of pranks plagues the kids. Could Sherlock have come to life-or is someone less frosty behind everything?